2020
DOI: 10.3390/biom10121640
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Conversion of Trilobolide into the Payload of Mipsagargin: 8-O-(12-Aminododecanoyl)-8-O-Debutanoylthapsigargin

Abstract: In spite of the impressing cytotoxicity of thapsigargin (Tg), this compound cannot be used as a chemotherapeutic drug because of general toxicity, causing unacceptable side effects. Instead, a prodrug targeted towards tumors, mipsagargin, was brought into clinical trials. What substantially reduces the clinical potential is the limited access to Tg and its derivatives and cost-inefficient syntheses with unacceptably low yields. Laser trilobum, which contains a structurally related sesquiterpene lactone, trilob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Thus far, a large number of natural compounds have been identified to have anti-tumor effects. The action mechanisms of these compounds are varied, including inducement of endoplasmic reticulum stress and cell cycle arrest, inhibition of ATPase and protein synthesis, and promotion of apoptosis [ 30 , 31 , 32 , 33 , 34 ]. Ginsenosides, the main active ingredients in ginseng, have been suggested to have therapeutic effects on a variety of human diseases, such as senescence, hyperglycemia, hypertension, hypoimmunity, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, a large number of natural compounds have been identified to have anti-tumor effects. The action mechanisms of these compounds are varied, including inducement of endoplasmic reticulum stress and cell cycle arrest, inhibition of ATPase and protein synthesis, and promotion of apoptosis [ 30 , 31 , 32 , 33 , 34 ]. Ginsenosides, the main active ingredients in ginseng, have been suggested to have therapeutic effects on a variety of human diseases, such as senescence, hyperglycemia, hypertension, hypoimmunity, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, PS can be modified by ligands increasing cell specificity of PS drugs [40,41]. Such active targeting can be achieved by modification with specific antibodies, nanobodies, affibodies, peptides, aptamers [42], androgens [43], or natural products such as sesquiterpene lactones and their derivatives [44][45][46]. Besides nanoparticles, liposomes are also a viable alternative for PS targeted delivery.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Sesquiterpenes were known to exhibit anti-cancer properties [16]. Currently, thapsigargin and trilobolide are leading sesquiterpene lactones in anticancer therapy [17,18]. It has been reported that costunolide possesses a variety of biological properties, such as anti-oxidant [19], anti-inflammatory [20], anti-allergic [21], neuroprotective [22], antimicrobial [23], anti-cancer [24], and bone remodeling [25] effects.…”
Section: Introductionmentioning
confidence: 99%